El desconocimiento de derechos y la necesidad económica de los trabajadores ocasiona la explotación laboral, en la ciudad de Guaranda, año 2021. - Naranjo Bonilla, Sandro Sebastián (2023)
In the current topic of research carried out, the main topic to be addressed "Ignorance of rights and the economic need of workers causes labor exploitation, in the city of Guaranda, Bolívar province in the year 2021" mentions the general objective of carrying out a study on the lack of knowledge of the rights and the economic need of the workers causes labor exploitation, after the analysis of the causes of the lack of knowledge of the rights and the economic need of the workers causes the labor exploitation and the formulation of criteria on the consequences that generates the ignorance of the rights and the economic need of the workers causes labor exploitation, in the city of Guaranda, Bolívar province in the year 2021, with this the elaboration of a legal proposal aimed at socializing the rights that the workers have. It consists of a viable project, which arises from a lack of consideration and respect for the workers and the arbitrary and illegal labor exploitation exercised by the employers in order to suit their interests, which leads to the violation of the rights that the worker must receive in accordance with what establishes the Constitution of the Republic of Ecuador, the Labor Code and international agreements, with the possibility that the argumentation made on labor exploitation in its direct relationship with the individual work contract, constitutes a useful reference instrument for disseminate the rights that assist workers, the information on our subject of study was obtained thanks to the doctrine and advice obtained by those responsible in the Ministry of Labor and Employment of Guaranda and judicial officials of the 4 respective judicial unit of the city , to conclude the practical application of the subject of study was carried out, which has determined do so that it is recommended to disseminate labor rights and principles. In Ecuador, working hours meet a parameter of hours established in what according to the Labor Code, they must be eight hours a day in what does not exceed forty hours a week, but after some exceptions for what the contractor stipulates there are overtime Most of them should be paid, but after not presenting principles of legality in the stipulated employment contracts, this parameter is not respected in the country, accustoming the employee to not respecting their own rights due to the lack of knowledge before them, on the other hand there are also special shifts of shorter duration, so the working day is six hours and only for additional or extra recovery hours can they be extended. Therefore, the salaries by the state in both public and private companies are divided by their daily values as employees, workers and even including what are monthly values as basic salary before reducing taxes and various discounts between overtime, commissions, reward bonuses, transportation and among others. Mixed investigative methods will be used as qualitative when measuring the investigative parameters that show the main causes of labor informality and also quantitative so that, through statistical data, the main factors in 2021 that sanctioned caused the ignorance of the rights are evaluated. In addition to the factors to trigger the emerging problem in regard to labor exploitation, the referenced sample is for convenience since a total number of 20 workers in the city of Guaranda was considered.